О размещении и численности массовых видов каменок (Oenanthe) в Южном Закавказье - Тарасов, М.П. (Вестник зоологии, 1975)
Of six Oenanthe species occurring in the open landscapes of southern Transcaucasia O. isabellina Temm., O. oenanthe L. and O. finschi Heugl. are most numerous and widely distributed. Peculiarities in vertical and biotopical distribution of these species are traced. The data on the number of the birds, times of their arrival and flying away are given.